The Effects of the Supplementation with Snakehead Fish and Sea Cucumber Extracts on Platelet-Derived Growth Factor in Post-Operative Patients - Otniel Wendy Wahono; JB. Suparyatmo; Dian Ariningrum (INDONESIAN JOURNAL OF CLINICAL PATHOLOGY AND MEDICAL LABORATORY, 2020)
Wound healing is a complex process that involves the interaction between Extracellular Matrix (ECM) cells and mediated by cytokines and various growth factors, especially platelet-derived growth factor (PDGF) which plays a role in almost every phase of wound healing. Applying snakehead fish and sea cucumber extract containing amino acids and fatty acids in post-operative patients is expected to increase PDGF levels and enable the acceleration of the wound healing process. This study was a double-blind randomized control trial with a pre and post-treatment approach which involved 34 post-operative patients divided into two groups; the control group (K1) and treatment group (K2) and was carried out from April to June 2019 at Dr. Moewardi Hospital in Surakarta. Independent sample T-test was used for data with normal distribution to determine the mean differences between the control and treatment groups, while the Mann-Whitney test was used for data with the abnormal distribution. Also, to determine the mean difference before and after the treatment of one paired group, a paired T-test was used for data with normal distribution, while the Wilcoxon test was used for data with the abnormal distribution. p < 0.05 was significant with 95% Confidence Intervals (CI). The supplementation of snakehead fish and sea cucumber extract significantly increased PDGF levels in the treatment group (K2) compared to the controls group (K1) (p <0.001). Our findings showed that snakehead fish and sea cucumber extract were able to increase PDGF levels in post-operative patients on the fourth day.